Five year-old preschool children's perceptions of a friend - Gutierrez, Blanquita Icaro
This descriptive qualitative study aimed to explore how five-year-old preschool children perceive a friend and the differences among the children's perceptions of a friend across gender. Thirty-four (34) children, 17 male and 17 female, enrolled at the University of the Philippines Child Development Center, with ages 5.0-5.11 were selected through random sampling. They were observed for 3 days in their respective classes. The respondents were then interviewed about their definition of a friend, perceived activities done by friends, and reasons for having a friend. Pictures were used to aid the children in explaining their perceived determinants of friendship. The children's responses were analyzed through coding, frequency and percentage count. For the definition of a friend, 55.88% of the respondents defined a friend as the word itself and other synonymous words such as best friend and kaibigan. Eleven out of 34 respondents (32.35%) gave responses related to play or playing when asked about their preference in a friend. Among the mentioned activities that are done together by friends, play was the most common activity identified with 30 out of 34 (94.2%) respondents mentioning it. The most common reason for having a friend was preference. Lastly, most of the respondents (85.29) regarded mutual sharing as a determinant of friendship. Based on the results, there were similarities and differences among male and female perceptions of a friend. These were reflected by the themes which emerged from both the male and female respondents and themes which appeared only among male or only among female. This study poses implications on the participation of teachers and parents in the development of friendship among children, implementation of preschool programs, and future studies that can be done.